Karakteristik Masyarakat Desa Jatirejoyoso Mengenai Perilaku Buang Air Besar Sembarangan - Lustyafa Inassani Alifia (CoMPHI Journal: Community Medicine and Public Health of Indonesia Journal, 2020)
Introduction: The proportion of open defecation behavior in Indonesia ranks second highest after India. Stop open defecation is the first pillar of the Community-Led Total Sanitation (CLTS) program as the main focus. Disposing feces that not eligible with sanitation requirements can cause soil pollution, the provision of clean water, and trigger the disease vectors. Aim of study: This study describes the characteristics of the people in Jatirejoyoso Village, Kepanjen District, Malang Regency regarding the ownership of healthy latrines, and the behavior of open defecation. This research sample was taken using a purposive sampling method of 46 households. Results and Discussion: The results showed 42 respondents (91.3%) understood the importance of healthy latrines. Meanwhile, 32 respondents (69.56%) behaved defecate in the river, and 14 (30.44%) of respondents conducted defecation in a neighbor's toilet. Residents who don’t have latrines because of the cost factor, as many as 40 respondents (86.96%), and the remaining 6 respondents due to lack of house land. 28 respondents (60.86%) experienced diarrhea within 1 year. All respondents (100%) claimed to have received information about BABS and PHBS from health workers in the village. Conclusion: The conclusion that can be drawn is the knowledge of the people of Jatirejoyoso Village about the importance of good healthy latrines, but the cost and land constraints are a factor for residents not to have private healthy latrines.